Comorbidities and Complications in Adult Peritonsillar Abscess Tonsillectomy Patients - Gawel, Erin M.; Corbin, Alexandra F.; Varavenkataraman, Gaayathri; Clausen, Sean; Carr, Michele M. (International Archives of Otorhinolaryngology, 2025)
Tonsillectomy is often used to treat recurrent tonsillitis (RT), but it is less commonly performed to treat peritonsillar abscess (PTA). While most PTAs are treated with needle aspiration or incision and drainage, quinsy tonsillectomy is used in select cases.To compare clinical characteristics and postoperative outcomes of patients undergoing quinsy tonsillectomy for PTA versus those undergoing tonsillectomy for RT.The American College of Surgeons NSQIP database was used to identify adults who underwent tonsillectomy (CPT code 42826) with a diagnosis of either PTA or RT. Data was collected from 2018–2021. Demographics, comorbidities, risk factors, postoperative complications, and outcomes including operative time, length of stay (LOS), readmission, and reoperation were compared. Logistic regression identified predictors of readmission and reoperation.10241 patients had RT and 366 had PTA. PTA patients had significantly higher rates of smoking (27.0% versus 12.3%), diabetes (6.6% versus 2.5%), hypertension (11.5% versus 5.8%), and preoperative sepsis (14.5% versus 0.3%; p < .001 for all). Operative time and LOS were longer in the PTA group (33.5 minutes versus 25.8 minutes; 2.5 days versus 0.2 days, respectively; p < .001 for both). Despite higher rates of rare complications like ventilator use (0.8% versus 0.0%) and sepsis (2.2% versus 0.0%; p < .001 for both), no significant differences were observed in postoperative hemorrhage, readmission, or reoperation.Adults undergoing quinsy tonsillectomy for PTA have more comorbidities and rare complications compared with RT patients, likely due to active infection. However, the procedure is not linked to increased hemorrhage risk and remains safe treatment.
Keywords: peritonsillar abscess; recurrent tonsillitis; chronic tonsillitis; quinsy tonsillectomy; postoperative complications